Antimicrobial interventions to reduce Salmonella and Campylobacter populations and improve shelf life of quail carcasses - A. Rincon; S. Kumar; C.W. Ritz; J.S. Jackson; C.R. Jackson; J.G. Frye; A. Hinton, Jr.; M. Singh; D.E. Cosby; N.A. Cox; H. Thippareddi (Poultry Science, 2020)
Quail (Coturnix japonica) is processed and marketed as fresh meat, with limited shelf life. The objective of this study was to evaluate the efficacy of antimicrobial interventions during slaughter on reducing Salmonella and Campylobacter contamination and to determine the microbiological shelf life of quail during refrigerated (4°C) storage. Three antimicrobials, peracetic acid (400 ppm; PAA), Citrilow (pH 1.2), and Cecure (cetylpyridinium chloride [CPC], 450 ppm), along with a water and no-treatment control were evaluated. Quail carcasses (n = 75) were inoculated with a cocktail of nalidixic acid–resistant Salmonella Typhimurium and gentamicin-resistant Campylobacter coli. After 30 min of attachment time, quail carcasses were submerged in each antimicrobial solution for 20 s with air agitation. Noninoculated quail carcasses (n = 25) were similarly treated, packaged, and stored under refrigeration (4°C). Aerobic plate counts (APC), psychrotroph counts (PC), Enterobacteriaceae counts (ENT), total coliform counts (TCC), and Escherichia coli counts on quail carcasses were determined on 1, 4, 7, and 10 d. Salmonella and Campylobacter populations were determined by plating on Petrifilm APC supplemented with 200-ppm nalidixic acid and Campy Cefex agar supplemented with 200-ppm gentamycin, respectively. No significant reductions in (P > 0.01 log cfu/mL) in APC, PC, ENT, TCC, and E. coli counts were observed on carcasses submerged in water. However, treatments with PAA, Citrilow, and CPC significantly reduced (P ≤ 0.05) Salmonella and Campylobacter coli contamination. Citrilow showed greater (P ≤ 0.05) reduction in Salmonella and Campylobacter population (1.90 and 3.82 log cfu/mL reduction, respectively) to PAA and CPC. Greater (P ≤ 0.05) reductions in APC, PC, ENT, TCC, and E. coli counts (2.22, 1.26, 1.47, 1.52, and 1.59 log cfu/mL, respectively) were obtained with the application of CPC. Application of antimicrobial interventions resulted in a reduction in Campylobacter and Salmonella, APC, PC, and ENT populations after treatments (day 0) and throughout the storage period (day 10). Use of antimicrobial interventions after slaughter can improve the microbiological safety and shelf life of quail.